Education as a Lifelong Process : the german Educational Panel Study (NEPS) - Blossfeld, Hans-Peter [Verfasser]; Rossbach, Hans-Günther [Verfasser]; Maurice, Jutta von [Verfasser] (VS Verl. für Sozialwissenschaften, 2011)
"Like other modern industrialized societies, Germany has evolved into a knowledge-based enonomy in which the role of education and educational institutions has become a key factor in all phases of the life course. More than ever befor, education has become a lifelong process in which individuals continue to learn in formal, nonformal an informal environments throughout their lives. As a result, their educational careers and competencies and how these unfold in relation to the family, educational institutions, workplaces, and private life have become a topic of major national interest. Understanding what is happening over the life course requires a longitudinal approach. This ist why the National Educational Panel Study (NEPS) for the Federal Republic of Germany has been set up to collect longitudinal data on educational processes and competence development within a multicohort sequence design, and to make this data available to the scientific community. The 20 chapters in this special issue deliver valuable information on the conception of NEPS, how it is embedded in the research landscape, its major theoretical dimensions, the educational stages being analyzed, along with several interesting methodological aspects and data protection issues." (Verlag, BIBB-Doku)
Keywords: G 1.3.2 Bildungsverhalten und -verläufe; G 1.2.3 Qualifikationsentwicklungen; S 4.3.5 Bildungsbeteiligung & soziale Gerechtigkeit; S 4.3.6 Human Capital; G 1.3.2.2 Übergänge; S 1.5 Weiterbildung; T 3 Forschungsmethoden; Nationales Bildungspanel; Bildungsverlauf; Lebensverlauf; Kompetenzentwicklung; Soziale Ungleichheit; Bildungschance; Bildungsertrag; Berufseinmündung; Erwachsenenbildung; Lebenslanges Lernen; Bildungsforschung; Längsschnittuntersuchung